ALGORITMIK TILLAR VA DASTURLASh FANINI O‘QITIShDA SUN’IY INTELLEKTLARDAN FOYDALANISh METODIKASI - Qunnazarov, A.Q. (SCIENCE and SOCIETY, 2025)
The article analyzes the methodology of using artificial intelligence tools in teaching algorithmic languages and modern programming. It examines the role of algorithmic languages in the educational process and provides statistics on the use of Python, Java, C++, and JavaScript programming languages. The article also assesses their role in education and analyzes the advantages of artificial intelligence-based learning tools.
Keywords: algorithmic languages; programming languages; Python; Java; C++; JavaScript; artificial intelligence; methodology; learning process; learning effectiveness; modern technologies